Effects of Mn-dopant on phase, microstructure and electrical properties in Bi3.25La0.75Ti3O12ceramics - Pasinee Siriprapa (2018)
Lanthanum-doped bismuth titanate (Bi3.25La0.75Ti3O12or BLT) is important ferroelectric materials for FeRAMS, which need further improved by substituting isovalent cations to assist the elimination of defects such as oxygen vacancy. In this work, fabrication and investigation of substituting Mn4+for Ti4+ion on B-site of Bi3.25La0.75Ti3O12ceramics were carried out. X-ray diffraction patterns of BLTMn ceramics indicated orthorhombic structure with lattice distortion, especially for samples with higher concentration of MnO2dopant. Microstructural investigation showed that all ceramics composed mainly of plate-like grains. An increase in MnO2doping content increased diameter and thickness of grains but reduced density of the ceramics. Electrical conductivity was found to decrease while dielectric constant increased with Mn4+doping concentration. © 2012 Elsevier Ltd and Techna Group S.r.l.